Silencing of HLA class I on primary human hepatocytes as a novel strategy for reduction in alloreactivity. Issue 8 (10th June 2019) - Figueiredo, Constança; Oldhafer, Felix; Wittauer, Eva‐Maria; Carvalho‐Oliveira, Marco; Akhdar, Ali; Beetz, Oliver; Chen‐Wacker, Chen; Yuzefovych, Yuliia; Falk, Christine S.; Blasczyk, Rainer; Vondran, Florian W.R.
Abstract: In contrast to the whole liver, primary hepatocytes are highly immunogenic. Thus, alternative strategies of immunomodulation after hepatocyte transplantation are of special interest. Silencing of HLA class I expression is expected to reduce the strength of allogeneic immune responses and to improve graft survival. In this study, primary human hepatocytes (PHH) were isolated using a two‐step‐collagenase perfusion‐technique and co‐cultured with allogeneic lymphocytes in terms of a mixed lymphocyte hepatocyte culture. Expression of HLA class I on PHH was silenced using lentiviral vectors encoding for β2‐microglobulin‐specific short hairpin RNA (shβ2m) or non‐specific shRNA (shNS) as control. The delivery of shβ2m into PHH caused a decrease by up to 96% in β2m transcript levels and a down‐regulation of HLA class I cell surface expression on PHH by up to 57%. Proliferative T cell alloresponses against HLA‐silenced PHH were significantly lower than those observed form fully HLA‐expressing PHH. In addition, significantly lower secretion of pro‐inflammatory cytokines was observed. Levels of albumin, urea and aspartate‐aminotransferase did not differ in supernatants of cultured PHH. In conclusion, silencing HLA class I expression on PHH might represent a promising approach for immunomodulation in the transplant setting without compromising metabolic function of silenced hepatocytes.